Editor's Introduction: Paradigm Shift in Optic Neuropathy: Early Insights into Precise Etiological Differentiation - Indra Tri Mahayana, MD, PhD (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2026)
Due of its heterogeneity in etiology, including inflammatory, vascular, and traumatic causes rather than as a singular condition and individual disease, the global prevalence of non-glaucomatous optic neuropathy (NGON) continues to be a challenging scientific difficulty.1,2,3 A retrospective study was performed at a tertiary eye‑care center in Yogyakarta, Indonesia, covering the period between January 2019 to December 2023 (4 years investigation period, including in the COVID-19 era). Read more >>>